Will the FIFA bribery scandal spur money laundering law reform in Hong Kong?: Comparing Hong Kong's Anti-Money Laundering Regime with Financial Action Task Force Recommendations. (2nd January 2016) - Lee, Emily
Abstract : The article first explains why the anti-money laundering (AML) regime in Hong Kong concerns cross-discipline and cross-jurisdiction issues. The author uses the recent money laundering scandal involving The Fédération Internationale de Football Association (FIFA) members as an opportunity to assess the Financial Action Task Force (FATF) Recommendations on politically exposed persons (PEPs). The FIFA scandal involved financial institutions acting as intermediaries in facilitating the PEPs' money laundering activities. Given financial institutions' knowing or unknowing involvement in the scandal, there appears to be significant gaps in financial institutions' 'know your clients' (KYC) due diligence process. The article warns that regulation on this issue is fragmented and inconsistent, as evidenced by how the risk-based approach recommended by the FATF is not observed in every jurisdiction. The article then examines the anti-money laundering regime in Hong Kong, one of the world's main financial centres, by examining its various legislation and comparing them with the FATF Recommendations. Lastly, the article suggests improvements to Hong Kong's AML legislation and the FATF Recommendations which are essentially a set of global AML standards. The article then explores ways to better implement the FATF Recommendations in jurisdictions that have adopted them, especially those which host the world's financial centres.